Vascular endothelial growth factors: A comparison between invertebrates and vertebrates. Issue 6 (December 2015) - Kipryushina, Yulia O.; Yakovlev, Konstantin V.; Odintsova, Nelly A.
Abstract: This review aims to summarize recent data concerning the structure and role of the members of the vascular endothelial growth factor (VEGF) and vascular endothelial growth factor receptor (VEGFR) families in the context of early development, organogenesis and regeneration, with a particular emphasis on the role of these factors in the development of invertebrates. Homologs of VEGF and/or VEGFR have been found in all Eumetazoa, in both Radiata and Bilateria, where they are expressed in the descendants of different germ layers and play a pivotal role in the development of animals with and without a vascular system. VEGF is a well-known angiogenesis regulator, but this factor also control cell migration during neurogenesis and the development of branching organs (the trachea) in invertebrate and vertebrate species. A possible explanation for the origin of Vegf/Vegfr in the animal kingdom and a pathway of Vegf/Vegfr evolution are discussed.